42.1k views
0 votes
What is the sum of the rational expression

What is the sum of the rational expression-example-1

2 Answers

4 votes


\bf \cfrac{x}{x+1}+\cfrac{6x}{x+5}\implies \stackrel{\textit{our LCD will be (x+1)(x+5)}}{\cfrac{(x+5)x~~~~+~~~~(x+1)6x}{(x+1)(x+5)}}\implies \cfrac{x^2+5x~~+~~6x^2+6x}{(x+1)(x+5)} \\\\\\ \cfrac{7x^2+11x}{(x+1)(x+5)}\implies \cfrac{7x^2+11x}{x^2+6x+5}

User Alexey Popkov
by
6.0k points
4 votes

The answer would be B.

Add across : x + 6x = 7x

(x + 1) + (x + 5) = 2x + 6

So you get 7x / 2x + 6

User Jbafford
by
5.6k points